Akad Qardh dan Wakalah Bil Ujrah Dalam Transaksi Financial Technology Syari’ah Peer to Peer Lending: - Nurman Ferdiana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
In order to prepare the technological infrastructure of developing countries like Indonesia. Information and transactions that can be accessed directly by the general public requires effectiveness and efficiency in feature items, especially technology development. Financial Technology (Fintech) has gone viral because it is one of the best technology options in the financial sector. The conveniences that are obtained by the actors or consumers are aimed at creating independent satisfaction but it is necessary to have a valid contract that will be used and this concerns prospects which have very large implications for the world of financing. Besides these changes, there are various kinds of problems that have arisen, especially the concept of implementing qardh contracts in peer to peer lending syari'ah, applying wakalah bil ujrah contracts in peer to peer lending syari'ah and applying qardh contracts and wakalah bil ujrah in peer to peer lending. syari'ah in the perspective of the DSN-MUI fatwa number 117/DSNMUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. So that the objectives achieved can analyze the concept of the validity of the application of the contract. As well as the final analysis of the DSN-MUI fatwa on sharia peer to peer lending.. The type of research used by researchers is qualitative to obtain data using library research (library research). The nature of the research is descriptive. DSN-MUI fatwa number 117/DSNMUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles which forms the basis is correct, but requires specific fatwas so that the certainty of the application of contracts to service products is more certain and there is no usury and gharar in invoice financing productive and consumer This regulation deserves to be studied, understood and revised by the Government, in this case the Financial Services Authority, DSN-MUI, in issuing regulations and fatwas that accommodate the legitimacy of how fintech products work. This requirement is a form of responsibility of the two regulators so that the risk of occurrence which is prohibited by Syar'I cannot be realized (safe to use). Product contract clauses must be spelled out directly when making a financing contract. So as to be able to support sharia by investing legally, safely, lawfully and can help those in need, especially in funding needs. For this reason, the DSN-MUI fatwa No. 117/DSNMUI/II/2018 must explain in detail the design and achievements determined through collective ijtihad (ijtihad jama'i) so that a National Sharia Council - Indonesian Ulema Council rule is issued which is competent and can fulfill simple elements. , clear, and can be used and understood by startups. Keywords: Financial Technology, Fintech, Fatwas.